(untitled) (Research, Society and Development, 2021)
Since the neolithic period, when man realized that it could transform the natural landscape and become sedentary, that the Bio business has intensively marked an anthropic action in the natural environment. Food production started as a source of survival, after then, with the introduction and discovery of new technics there was an advancement in cultivation, which generated more than enough for self-consumption. In this context, the research has done a historical approach to coffee implantation, which is very important to the country, the biggest coffee bean production in the world. In this perspective, the purpose of this study is to understand the physical and landscape coffee arrangement production at Fazenda Vidigal, in Barra do Choça, BA, trying to identify the technological advance and the facilities, equipment and people involved. This is about a qualitative study to locate the property and describe the spatial structure of a coffee farm. It was used crossed information of exploratory bibliographic analysis and field research. These arrangements further the constant development of coffee farming at a prominent region in the national and international scenery because of the coffee quality, unique way to plant, farm, production, harvest, until the exportation.